1990
DOI: 10.1111/j.1464-410x.1990.tb14964.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Bony Metastases in Prostatic Carcinoma

Abstract: Fifty-five prostate cancer and 55 breast cancer patients with positive bone scintigrams were studied. The pattern of spread in the axial skeleton and pelvis showed differences between the 2 groups. This difference was not related primarily to bone volume at the site of metastasis. The difference in distribution of bony metastases between breast and prostate is explained by our knowledge of Batson's vertebral venous plexus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…23 Another study reported dedifferentiation in 68% of tumors not treated with hormones between 2 subsequent TURP procedures with a mean interval of 2.4 years. 24 Wheeler et al 25 analyzed 49 patients who were initially treated with radiotherapy. After local recurrence of prostate cancer, a statistically significant shift to higher grades was seen.…”
Section: Discussionmentioning
confidence: 99%
“…23 Another study reported dedifferentiation in 68% of tumors not treated with hormones between 2 subsequent TURP procedures with a mean interval of 2.4 years. 24 Wheeler et al 25 analyzed 49 patients who were initially treated with radiotherapy. After local recurrence of prostate cancer, a statistically significant shift to higher grades was seen.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the lumbar part of the spine was the area most frequently affected by metastases; next were the thoracic and cervical portions. The level of the vertebral column involved by the metastatic process is not primarily related to the amount of bone [5]. Additional venous pathways (Batson veins) for hematogenous metastases may also contribute to the high frequency of lumbar metastases [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…However, in almost a quarter of the cases, oral metastasis was found to be the first indication of an occult malignancy at a distant site [9]. CTC may bypass the filtration of the lungs through the valveless vertebral venous plexus; increased intrathoracic pressure can direct blood flow into this system from the caval and azygous venous system accounting for the increased distribution of axial skeleton and head and neck metastasis [55,56]. In addition, because of their unusual plasticity, CTC may pass through the arteriovenous shunts in the lungs, seeding in distal organs.…”
Section: Metastasis To the Jaws And Oral Cavitymentioning
confidence: 99%